Dielectric, XPS, and ferromagnetic relaxation studies of Ho-substituted polycrystalline magnetic oxide materials. Issue 21 (1st November 2022) - Manzoor, Alina; Azhar Khan, Muhammad; Afzal, Amir Muhammad; Arshad, Muhammad Imran; Shahzad, Aamir; Akbar, Sofia; Kashif, Muhammad; Ashraf, Ghulam Abbas; Khan, Muhammad Yaqoob; Rasul, M. Nasir; Shifa, Muhammad Shahzad; Nasar, Gulfam; et al.
Abstract: The impact of holmium (Ho) ions on lithium-rich spinel ferrites is studied through magnetic, morphological, and electrical transport properties. The X-ray photoelectron spectroscopy (XPS) analysis indicated the existence of all metal ions in the required valence state. Transmission electron microscopy (TEM) analysis exhibited nano-crystalline (∼50 nm) structures of these ferrites. The electrical resistivity measurements showed the higher resistivity values of the synthesized samples. The resistivity increased from 2.4 × 10 8 to 2.1 × 10 10  Ω-cm with Ho inclusion, indicated an inverse relation with the size of grains. The Curie temperature ( T c ) observed to decrease from 848 to 806 K with the incorporation of Ho 3+ ions. The activation energy (Δ E a ) noted to vary between 0.21 and 0.23 eV. The drift mobility ( μ d ) study revealed a decrease from 1.86x10 −12 to 6.14x10 −14 cm 2 V −1 s −1 by increasing Ho amount up to x = 0.06. A reduction in thermoelectric power (S) from -143 to -95 μ.V/K by increase in Ho concentration confirmed the Fe replacement by Ho on octahedral B-sites. The ferromagnetic resonance (FMR) investigations indicated a drop in FMR line-broadening (ΔH) from 2491 to 2000 Oe by the increase of Ho concentration, making it beneficial to reduce microwave losses. A non-linear variation in the resonance field ( H res ) with the substitution of Ho was observed between 7359 to 7785 Oe.